A checklist of bark and ambrosia beetles (Coleoptera: Scolytidae and Platypodidae) from Siberia and the Russian Far East - Legalov, Andrei A. (Acta Biologica Sibirica, 2022)
Currently, 185 species of the family Scolytidae and three species of the family Platypodidae are recorded from Asian Russia. In total, 99 species of bark beetles are found in Siberia and 168 species in the Russian Far East. Platypodidae are known anly from the south of the the Russian Far East. Two species of Scolytidae are found in Yamalo-Nenets Autonomous Okrug, 13 species in Khanty-Mansi Autonomous Okrug, 19 species in Tyumen Oblast, four species in Kurgan Oblast, three species in Omsk Oblast, 37 species in Tomsk Oblast, 28 species in Novosibirsk Oblast, 32 species in Kemerovo Oblast, 25 species in Altay Krai, 53 species in Altai Republic, 62 species in Krasnoyarsk Krai, 11 species in Republic of Khakassia, 24 species in Tyva Republic, 55 species in Irkutsk Oblast, 61 species in Buryatiya Republic, 40 species in Zabaikalskii Krai, 52 species in Sakha (Yakutia) Republic, 25 species in Kamchatka Oblast, one species in Chukotka Autonomous Okrug, 19 species in Magadan Oblast, 45 species in Amur Oblast, one species in Jewish Autonomous Oblast, 67 species in Khabarovsk Krai, 130 species in Primorsky Krai, 87 species in Sakhalin Is. and 68 species in Kuriles Isl.